Prepotent task-irrelevant semantic information is dampened by domain-specific control mechanisms during visual word recognition. Issue 3 (March 2022) - Sulpizio, Simone; Job, Remo; Leoni, Paolo; Scaltritti, Michele
We investigated whether semantic interference occurring during visual word recognition is resolved using domain-general control mechanisms or using more specific mechanisms related to semantic processing. We asked participants to perform a lexical decision task with taboo stimuli, which induce semantic interference, as well as a semantic Stroop task and a Simon task, intended as benchmarks of linguistic-semantic and non-linguistic interference, respectively. Using a correlational approach, we investigated potential similarities between effects produced in the three tasks, both at the level of overall means and as a function of response speed (delta-plot analysis). Correlations selectively surfaced between the lexical decision and the semantic Stroop task. These findings suggest that, during visual word recognition, semantic interference is controlled by semantic-specific mechanisms, which intervene to face prepotent but task-irrelevant semantic information interfering with the accomplishment of the task's goal.